1998
DOI: 10.2307/3870615
|View full text |Cite
|
Sign up to set email alerts
|

A Recessive Heterochronic Mutation, plastochron1, Shortens the Plastochron and Elongates the Vegetative Phase in Rice

Abstract: We describe two recessive alleles of a rice heterochronic gene, plastochron1-1 (pla1-1) and pla1-2, that reduce the length of the plastochron to approximately half that of the wild type. Because the onset of the reproductive phase in pla1 was not temporally affected, the number of leaves produced in the vegetative phase was nearly twice that produced in the wild type. Panicle development was severely disturbed in pla1 mutants. In pla1-1, many primordia of primary rachis branches were converted into vegetative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 12 publications
4
53
0
Order By: Relevance
“…CYP78A5, also known as KLUH, has recently been implicated in growth regulation, with small leaves and floral organs in cyp78a5 mutants because of prematurely arrested growth (Anastasiou et al, 2007), similar to what was shown for the apparent rice ortholog, PLA1 (Itoh et al, 1998). We found that Pro35S:MIR156f plants, which have a similar plastochron phenotype to cyp78a5 mutants, also exhibited smaller leaf size (Table 1; see Supplemental Figure 5 online).…”
Section: Effects Of Cyp78a5/kluh and Cyp78a7 On Plastochron Lengthsupporting
confidence: 54%
See 2 more Smart Citations
“…CYP78A5, also known as KLUH, has recently been implicated in growth regulation, with small leaves and floral organs in cyp78a5 mutants because of prematurely arrested growth (Anastasiou et al, 2007), similar to what was shown for the apparent rice ortholog, PLA1 (Itoh et al, 1998). We found that Pro35S:MIR156f plants, which have a similar plastochron phenotype to cyp78a5 mutants, also exhibited smaller leaf size (Table 1; see Supplemental Figure 5 online).…”
Section: Effects Of Cyp78a5/kluh and Cyp78a7 On Plastochron Lengthsupporting
confidence: 54%
“…By comparing endogenous expression domains of SPL genes with the results of misexpression studies, we demonstrate that miR156 limits plastochron length in developing leaf primordia. The effects of miR156/SPLs on leaf initiation rate appear to be independent of CYP78A5/KLUH, a likely ortholog of rice PLA1 (Itoh et al, 1998;Zondlo and Irish, 1999;Miyoshi et al, 2004;Anastasiou et al, 2007). Interestingly, organ size and plastochron length are coordinately affected by both miR156/SPL and CYP78A5, suggesting either that there are common regulators of organ size and plastochron length or that these two developmental parameters reciprocally influence each other.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The initiation of lateral organ primordia is induced by a local auxin maximum accumulated in the peripheral zone of SAM, then next primodium formation may initiate at the site most distant to the preexisting primordium because the established primordia act as a sink to deplete auxin accumulation within surrounding cells [7][8][9][10]. Since changes in size and/or organization of SAM can alter the field in which auxin acts, a number of mutants exhibit close association of abnormal phyllotaxy with modified meristems [11][12][13][14]. The maize abphyl1 mutant has an enlarged SAM with abnormal phyllotaxy [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the inhibition effect of preexisting primodia may not only determine the site of leaf initiation, but also prevent the precocious development of new leaves [7,16]. However, the analysis of the rice plastochron1 mutant that shows decreased plastochron with normal phyllotaxy provided the insight of the disassociation between regulatory pathway governing spatial and temporal patterns of the leaf initiation [12,17]. Molecular analysis revealed that PLA1 encodes CYP78A11, a member of cytochrome P450 family involved in phytohormone biosynthetic pathways [17].…”
Section: Introductionmentioning
confidence: 99%